Implementasi Aplikasi Mobile HRIS Pada PT YKK Zipper Indonesia Menggunakan Metode Borg and Gall - Ruli, Ahmad Rais; Yani, Desri; Rio Sebastian, Dante (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System; Vol 8 No 2 (2023): INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS (Desember 2023)DO - 10.51211/isbi.v8i2.2676, 2023)
Human resources are organizational resources that need to be managed effectively and efficiently. The amount of information that needs to be managed related to human resources creates very complex problems. The importance of managing very complex human resources in a company makes the company have to form a new department, namely the Human Resources Department or Personnel Department. PT Ykk Zipper Indonesia is currently still using a desktop-based application Hris system where the obstacles of employees when submitting Overtime, Leave and Salary Slips must be in the office environment, from these problems researchers try to implement this mobile application it is hoped that the problem of submitting Overtime, Leave and mobile salary slips can be resolved. The research method is based on the Borg and Gall method. This method includes several steps to make a product. The results of this study are presented in the form of an application, according to this method the results of this application have only reached the initial stage of product development .